2017
DOI: 10.14744/less.2017.25744
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pneumoperitoneum pressure on blood gases, respiratory and venous systems during laparoscopic cholecystectomy: A prospective randomized trial

Abstract: Introduction: Increased abdominal pressure during pneumoperitoneum may distress respiratory functions and venous systems. The aim of this study was to evaluate the effect of low and high pneumoperitoneum pressure during laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…It should be noted that even mild hyperventilation can adversely affect the Fontan circulation since hyperventilation itself can increase airway pressure. Aksakal et al reported that 8 mmHg insufflation increased PaCO 2 from a mean value of 33.4 mmHg to 35 mmHg and, more interestingly, to 38.1 mmHg after the end of insufflation in adult patients without heart disease undergoing laparoscopic cholecystectomy [ 5 ]. They suggested IAP might suppress CO 2 absorption from the capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that even mild hyperventilation can adversely affect the Fontan circulation since hyperventilation itself can increase airway pressure. Aksakal et al reported that 8 mmHg insufflation increased PaCO 2 from a mean value of 33.4 mmHg to 35 mmHg and, more interestingly, to 38.1 mmHg after the end of insufflation in adult patients without heart disease undergoing laparoscopic cholecystectomy [ 5 ]. They suggested IAP might suppress CO 2 absorption from the capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a multitude of animal model studies on the physiological effects of pneumoperitoneum, the human body's specific response, particularly regarding changes in blood gases, respiratory, and venous systems, remains relatively unexplored. Moreover, the metabolic implications of pneumoperitoneum using CO 2 are not well documented, especially in COPD patients from Western countries and India [10]. Therefore, our research aims to investigate the changes in heart rate, mean arterial pressure, arterial and end-tidal CO 2 , and bicarbonate (HCO 3 ) during laparoscopic cholecystectomy in COPD patients, in order to contribute to the optimisation of anaesthetic management in this population.…”
Section: Introductionmentioning
confidence: 99%